Interfacial charge recombination of Os(II)-polypyridyl-resorcinol complex on oleic acid capped TiO2 surface: what determines the dynamics? - Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (New Journal of Chemistry, 2013)
Femtosecond transient absorption spectroscopic studies of an osmium(II)-polypyridyl-resorcinol complex, 1, on oleic acid capped TiO2 have been carried out and the results have been compared with our previous studies on poly(vinyl) alcohol capped TiO2. While on both these surfaces the complex exhibits a single exponential <120 fs injection, the back electron transfer reaction is slower on the oleic acid capped TiO2 surface early on while it is faster on the same surface at longer times than on poly(vinyl)alcohol capped TiO2. The probable origin of these disparate observations has been analyzed.